Phylostratigraphic Profiles in Zebrafish Uncover Chordate Origins of the Vertebrate Brain - Šestak, Martin Sebastijan (Mol Biol Evol, 2015)
An elaborated tripartite brain is considered one of the important innovations of vertebrates. Other extant chordate groups have a more basic brain organization. For instance, cephalochordates possess a relatively simple brain possibly homologous to the vertebrate forebrain and hindbrain, whereas tunicates display the tripartite organization, but without the specialized brain centers. The difference in anatomical complexity is even more pronounced if one compares chordates with other deuterostomes that have only a diffuse nerve net or alternatively a rather simple central nervous system. To gain a new perspective on the evolutionary roots of the complex vertebrate brain, we made here a phylostratigraphic analysis of gene expression patterns in the developing zebrafish (Danio rerio). The recovered adaptive landscape revealed three important periods in the evolutionary history of the zebrafish brain. The oldest period corresponds to preadaptive events in the first metazoans and the emergence of the nervous system at the metazoan–eumetazoan transition. The origin of chordates marks the next phase, where we found the overall strongest adaptive imprint in almost all analyzed brain regions. This finding supports the idea that the vertebrate brain evolved independently of the brains within the protostome lineage. Finally, at the origin of vertebrates we detected a pronounced signal coming from the dorsal telencephalon, in agreement with classical theories that consider this part of the cerebrum a genuine vertebrate innovation. Taken together, these results reveal a stepwise adaptive history of the vertebrate brain where most of its extant organization was already present in the chordate ancestor.